An optimized protocol for the preparation of oxygen-evolving thylakoid membranes from Cyclotella meneghiniana provides a tool for the investigation of diatom plastidic electron transport. Issue 1 (December 2017) - Kansy, Marcel; Gurowietz, Alexandra; Wilhelm, Christian; Goss, Reimund
Abstract Background The preparation of functional thylakoid membranes from diatoms with a silica cell wall is still a largely unsolved challenge. Therefore, an optimized protocol for the isolation of oxygen evolving thylakoid membranes of the centric diatomCyclotella meneghiniana has been developed. The buffer used for the disruption of the cells was supplemented with polyethylene glycol based on its stabilizing effect on plastidic membranes. Disruption of the silica cell walls was performed in a French Pressure cell and subsequent linear sorbitol density gradient centrifugation was used to isolate the thylakoid membrane fraction. Results Spectroscopic characterization of the thylakoids by absorption and 77 K fluorescence spectroscopy showed that the photosynthetic pigment protein complexes in the isolated thylakoid membranes were intact. This was supported by oxygen evolution measurements which demonstrated high electron transport rates in the presence of the artificial electron acceptor DCQB. High photosynthetic activity of photosystem II was corroborated by the results of fast fluorescence induction measurements. In addition to PSII and linear electron transport, indications for a chlororespiratory electron transport were observed in the isolated thylakoid membranes. Photosynthetic electron transport also resulted in the establishment of a proton gradient as evidenced by the quenching of 9-amino-acridine fluorescence. Because of their ability to build-up a light-driven proton gradient, de-epoxidation of diadinoxanthin to diatoxanthin and diatoxanthin-dependent non-photochemical quenching of chlorophyll fluorescence could be observed for the first time in isolated thylakoid membranes of diatoms. However, the ∆pH, diadinoxanthin de-epoxidation and diatoxanthin-dependent NPQ were weak compared to intact diatom cells or isolated thylakoids of higher plants. Conclusions The present protocol resulted in thylakoids with a high electron transport capacity. These thylakoids can thus be used for experiments addressing various aspects of the photosynthetic electron transport by, e.g., employing artificial electron donors and acceptors which do not penetrate the diatom cell wall. In addition, the present isolation protocol yields diatom thylakoids with the potential for xanthophyll cycle and non-photochemical quenching measurements. However, the preparation has to be further refined before these important topics can be addressed systematically.